(2S,4S)-3-Acryloyl-6-oxo-2-phenylperhydropyrimidine-4-carboxylic acid - Sandip K. Kundu; Mathew P. D. Mahindaratne; Brian Quinõnes; George R. Negrete; Edward R. T. Tiekink (Acta Crystallographica Section E, 2010)
In the title compound, C14H14N2O4, the central six-membered ring adopts a twisted boat conformation with the phenyl substituent occupying an orthogonal position [dihedral angle = 86.88 (11)°]. In the crystal, molecules are linked by carboxylic acid–carbonyl O—H...O and amide–carbonyl N—H...O hydrogen bonds, forming a three-dimensional network.